2020
DOI: 10.1038/s41598-020-68389-1
|View full text |Cite
|
Sign up to set email alerts
|

Two novel bacteriophage genera from a groundwater reservoir highlight subsurface environments as underexplored biotopes in bacteriophage ecology

Abstract: Although bacteriophages are central entities in bacterial ecology and population dynamics, there is currently no literature on the genomes of bacteriophages isolated from groundwater. Using a collection of bacterial isolates from an aquifer as hosts, this study isolated, sequenced and characterised two bacteriophages native to the groundwater reservoir. Host phylogenetic analyses revealed that the phages targeted B. mycoides and a novel Pseudomonas species. these results suggest that both bacteriophages repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…In addition, pronounced morphological diversity of bacteriophages with presumably lytic representatives has been found in granitic groundwater of up to 450 m depth 12 , and might be the result of recombination events, horizontal gene transfer, and lysogeny known to shape microbial communities of the subsurface 13 . The recent recovery of two novel bacteriophage genera with lytic genes from groundwater highlights the potential of subsurface environments for being huge reservoirs of previously unknown viruses 14 . Furthermore, a study on predominant Halanaerobium spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pronounced morphological diversity of bacteriophages with presumably lytic representatives has been found in granitic groundwater of up to 450 m depth 12 , and might be the result of recombination events, horizontal gene transfer, and lysogeny known to shape microbial communities of the subsurface 13 . The recent recovery of two novel bacteriophage genera with lytic genes from groundwater highlights the potential of subsurface environments for being huge reservoirs of previously unknown viruses 14 . Furthermore, a study on predominant Halanaerobium spp.…”
Section: Introductionmentioning
confidence: 99%
“…HMWF031 (GBAN PTU03211; coverage, 99%; identity, 60.4%) and Pseudomonas sp. B1(2018) (GBAN WP_116583222; coverage, 99%; identity, 61.7%), and less similarity to TerB of the first described member of the genus Lanavirus , i.e., the Pseudomonas phage Lana [ 29 ] (GBAN YP_009820378.1; coverage, 99%; identity, 50.3%). An amino acid sequence alignment with selected TerB proteins deduced from bacterial and phage genomes (i.e., e-values from 1e-53 to 3e-43) showed a distribution of homologous amino acids over the entire length of the protein, as demonstrated by the consensus sequence and identical amino acids in the individual sequences shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A search of the databases using megablast [ 24 ] indicated that the phage PMBT3 genome showed only low similarity at the nucleic acid level (i.e., coverage, 35%; identity, 81.7%) to Pseudomonas phage Lana [ 29 ] (GBAN NC_048166 [ 38 ]), which has a similar genome size of 88,342 bp. The resulting amino-acid-based phylogenetic GBDP tree generated with VICTOR [ 28 ] for the phages PMBT3, Lana, PMBT14, and 30 other Pseudomonas phages is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pronounced morphological diversity of bacteriophages with presumably lytic representatives has been found in granitic groundwater of up to 450 m depth [11], and might be the result of recombination events, horizontal gene transfer and lysogeny known to shape microbial communities of the subsurface [12]. The recent recovery of two novel bacteriophage genera with lytic genes from groundwater highlights the potential of subsurface environments for being huge reservoirs of previously unknown viruses [13]. Furthermore, a study on predominant Halanaerobium spp.…”
Section: Introductionmentioning
confidence: 98%